STUDI PENGGUNAAN FORMALIN PADA BAKSO DI KECAMATAN RATU SAMBAN KOTAMADYA BENGKULU - Juniar -; Darius -; Andwini Prasetya (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2014)
Meatballs is one of the favorite foods of society. Various opinions say that the meatballs contain artificial preservatives, one of which is formaldehyde (CH2O). Formalin is a solution that is colorless, pungent containing approximately 37 % formaldehyde in water and usually 10-15 % methanol added that functions as a stabilizer so as not occuri polymerized. The purpose of this study is to determine whether there is formaldehyde in the District of Ratu Samban meatballs in the Bengkulu City. The research method used was a survey of 11 samples of meatballs in the District Ratu Samban Bengkulu City. When the study was conducted  on August 2 to August 8 2012. This kind of research is a descriptive analytical overview of the presence of formaldehyde contained in the District of Ratu Samban meatballs in the Bengkulu City. The results showed that the highest production of meatballs reaches 40 kg on weekdays and 50 kg on Saturday and Sunday, while the yield was lowest for the sale of meatballs which produced 2 kg per day. The test results of 11 ( eleven ) meatball samples showed that the formaldehyde content in the District outstanding meatballs Ratu Samban of Bengkulu City.Keywords: meatballs, formalin, Ratu Samban District